Yo-Yo intermittent recovery test performances within an entire football league during a full season - Mohr, M.; Krustrup, P. (Journal of Sports Sciences, 2014)
The study examined Yo-Yo intermittent recovery level 2 (YYIR2) and submaximal YYIR1 test performances in 172 male semi-professional football players (age; 25.8 ± 4.1 years) representing all teams in a top league at pre-season, start-season, mid-season and end-season. YYIR2 performance was 847 ± 227 m (±SD) at pre-season and rose (P < 0.05) by 128 ± 113 m to 975 ± 205 m at start of season and further (P < 0.05) by 59 ± 102 m to 1034 ± 211 m at mid-season. Submaximal YYIR1 HR was 90.9 ± 4.2% HRmax at pre-season, which was higher (P < 0.05) than at start, mid and end of season (87.0 ± 3.9, 85.9 ± 4.1 and 87.0 ± 3.7% HRmax, respectively). Peak YYIR2 performance and minimum YYIR1 HR were 1068 ± 193 m and 85.1 ± 3.8% HRmax, respectively, with ~50% of the players peaking at mid-season. Top-teams and middle-teams had higher (P < 0.05) peak YYIR2 scores (1094 ± 205 and 1121 ± 152 m, respectively) than bottom-teams (992 ± 185 m). YYIR2 performance was 16% higher (P < 0.05) and YYIR1 HR was 1.4% HRmax lower (P < 0.05) for regular players than non-regular players at pre-season and remained lower (P < 0.05) throughout the season. Central defenders had poorer (P < 0.05) YYIR performances compared to other positional roles. In conclusion, YYIR performances are highly variable within a football league over a season and are influenced by league ranking, regularity of competitive play and playing position.